ESTIMASI MATERNAL HETEROSIS UNTUK BOBOT BADAN PADA POPULASI DOMBA SINTETIK - Gunawan, Benny (BERITA BIOLOGI, 2010)
An experiment was conducted to evaluate the performance of production traits of the synthetic population of Border Leicester x Merino crossbred. A comparison was made between the F2, F2.5, F3 generations ( synthetic population ) and Fl generation. Estimates the effects of maternal heterosis in the synthetic populations of Border Leicester x Merino crossbred were analyzed by the method of least squares for Birth Weight (BW), Weaning Weight (WW) and Yearling Weight (YW). Two kind of analyses were executed for each traits i.e. within Fl sire generation and within F2 sire generation. For each analysis, maternal heterosis was respectively calculated as twice the difference between the least squares means of F2 and F2.5 lambs and F2.5 and F3 lambs.Pool estimates of maternal heterosis effects were also calculated for each traits. Research results showed that there was no significant difference of BW between F2, F2.5 and F3 generation. Weaning Weight was significantly higher (P < 0,05) in the synthetic population as compared to the Fl generation. Yearling Weight (YW) was significantly higher in the F2 generation as compared to F2.5 and F3 generation at the level of 5% (P < 0,05 ) and the 10% level (P < 0,10 ) respectively. Within Fl sire generation,maternal heterosis effects were 12,65%, 3,4% and 1,67% for Birth Weight (BW), Weaning Weight (WW) and Yearling Weight(YW). From the analysis within F2 sire generation, maternal heterosis effects were 1% for BW, 4,49% for WW and 3,09% for YW.Pool estimates of maternal heterosis effects were 5,78%, 3,95% and 2,37% for BW, WW and YW respectively. These results indicated that the effect of maternal heterosis gradually declined from preweaning to postweaning periods. In general, the present estimates of maternal heterosis for body weights are in close agreement with previous publications.In order to gain maximum benefit from heterosis, these results suggest that in designing a crossbreeding program,especially in developing a new synthetic population, we should take into account not only individual heterosis effects but also all other different sources of heterosis such as maternal heterosis. Genetic methods presented in this paper can be used in the breeding program in Indonesia,especially in the development of the improved synthetic sheep population. However to the determine the superiority of synthetic population over the Fl generation, the overall comparison should be made on body weight, growth rate, survival rate and fertility traits.